Die zukun̈ftige Ausgestaltung der Direktzahlungen - Eine quantitative Analyse mog̈licher Reformen in einer erweiterten Europaïschen Union - Martin Banse; Ferdinand Nol̈le (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Reforming Direct Payments in the EU - A Quantitative Analysis for an Enlarged EUThe introduction of the current Common European Agricultural Policy in ten new member states in central and eastern Europe will be a major financial challenge for the European Union. On the basis of the partial equilibrium model ESIM this article analyses potential consequences of different options for a reformed CAP. While the impact on agricultural markets will be relatively small, the financial burden of a harmonisation of agricultural policies and an introduction of direct payments in the new member states has to be carried mainly by the old member states of the EU-15. The burden of the main net-payers, especially Germany, would be significantly lower, if CAP were reformed according to the proposals of the EU-Commission's Mid-term Report. However, the remaining negative impacts on world agricultural trade and on world market prices for agricultural products, clearly show the necessity of a further reform of the CAP.
Keywords: 330